Challenges and Opportunities of Cleaner Production on Sustainable Development - Giannetti, Biagio F.; Agostinho, Feni; Almeida, Cec ' ilia M.V.B.; Yang, Zhifeng; Liu, Gengyuan; Hancock, Linda (Journal of Environmental Accounting and Management, 2026)
The current world environmental challenges claim for actions towards a sustainable development. Humans demand huge amount of resources to support the chosen development pattern, and returns concentrated human-waste to be diluted by nature, making this relationship unbalanced. This situation becomes worse when the resources extracted are beyond their own natural capacity of replenishment, which jeopardizes the resources availability and all social related issues as described by the 17 sustainable development goals. There is a common sense about the need of rethinking about the world we want for today and future generations, and for this task, looking for more sustainable production systems is an important step to feed policy makers with reliable scientific data to support better-oriented public policies. This special issue brings research show cases focused on themes discussed during the 8th and 9th International Workshop Advances in Cleaner Production, including cleaner production technologies, resources efficiency, environmental management, ecological modeling and business sustainability report. The main goal of this paper collection is to collaborate for the advances of cleaner production for the most different scales as an important approach to achieve the needed sustainable development.